Splenic Dendritic Cells and Macrophages Drive B Cells to Adopt a Plasmablast Cell Fate - McNamara, Hayley A.; Lahoud, Mireille H.; Cai, Yeping; Durrant-Whyte, Jessica; O’Connor, James H.; Caminschi, Irina; Cockburn, Ian A. (Frontiers in Immunology, 2022)
Upon encountering cognate antigen, B cells can differentiate into short-lived plasmablasts, early memory B cells or germinal center B cells. The factors that determine this fate decision are unclear. Past studies have addressed the role of B cell receptor affinity in this process, but the interplay with other cellular compartments for fate determination has largely been ignored. Moreover, B cell fate decisions have primarily been studied using model antigens rather than complex pathogen systems, which potentially ignore multifaceted interactions from other cells subsets activated during infection. Here we address this question using a Plasmodium infection model, examining the response of B cells specific for the immunodominant circumsporozoite protein (CSP). We show that B cell fate is determined in part by the organ environment in which priming occurs, with the majority of CSP-specific B cell response being derived from splenic plasmablasts. This plasmablast response was predominately independent of T cell help, though gamma-delta T cells were required to help with the early isotype switching from IgM to IgG. Interestingly, selective ablation of CD11c+ dendritic cells significantly reduced the splenic plasmablast response in a manner independent of the presence of CD4 T cell help. Conversely, immunisation approaches that targeted CSP-antigen to dendritic cells enhanced the magnitude of the plasmablast response. Altogether, these data indicate that the early CSP-specific response is predominately primed within the spleen and the plasmablast fate of CSP-specific B cells is mediated directly by CD11c+ dendritic cells.